1997
DOI: 10.1111/j.1600-0447.1997.tb09917.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic options in Charles Bonnet syndrome

Abstract: The term 'Charles Bonnet syndrome' refers to visual pseudohallucinations occurring especially in elderly people with reduced visual acuity. Despite numerous case reports, few successful methods of treatment have been described. Therapies with classical neuroleptics, antidepressants or benzodiazepines have generally been found to be unpromising. Only with carbamazepine treatment has improvement been observed in a few cases. In the three cases reported here, we successfully treated the condition with the atypica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
7

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 16 publications
0
24
0
7
Order By: Relevance
“…Comprehensive treatment includes providing adequate information to patients and their families, increasing the patient's quality of life, and treating the cause or anxiety disorder secondary to the symptoms. Several anticonvulsant, antipsychotic, and antidepressant agents have been tried, including carbamazepine, valproate, gabapentin, levetiracetam, haloperidol, olanzapine, risperidone, mirtazapine, venlafaxine, citalopram, donepezil, melperone and ondansetron [24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Comprehensive treatment includes providing adequate information to patients and their families, increasing the patient's quality of life, and treating the cause or anxiety disorder secondary to the symptoms. Several anticonvulsant, antipsychotic, and antidepressant agents have been tried, including carbamazepine, valproate, gabapentin, levetiracetam, haloperidol, olanzapine, risperidone, mirtazapine, venlafaxine, citalopram, donepezil, melperone and ondansetron [24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Batra et al (1997) reported three cases of CBS which were successfully treated with the atypical neuroleptic melperone, but it is uncertain whether this will be con®rmed by other investigators. Thus, at present, several attempts are required to establish the treatment of CBS.…”
Section: Introductionmentioning
confidence: 90%
“…A continuación presentamos una síntesis de las terapias farmacológicas que a nuestro conocimiento se han reportado en la bibliografía médica 12,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] (cuadro 1).…”
Section: 35unclassified